Social Media Marketing through Instagram and Repurchase Intention: The Mediating Role of Customer Engagement - Freddy Pandapotan Simbolon; Verencia Law (Bina Nusantara University, 2022)
In the digital era, the presence of social media has a strategic function in marketing that can be optimized to strengthen the company’s competitiveness. Besides having an essential role in promoting products and services quickly and massively, social media is also effective in building relationships with customers. Therefore, the company’s ability to optimize social media is a key success factor in winning the competition. The research aimed to determine the effect of social media marketing through Instagram on repurchase intention mediated by customer engagement. The research applied a quantitative approach and involved a sample of 102 Kopi Chuseyo Instagram followers taken through a simple random sampling technique. Data were collected using a questionnaire. Then, a quantitative approach with path analysis was used to analyze the research data. Research findings show that social media marketing has a significant effect on customer engagement and repurchase intention. The findings also mention that customer engagement affects repurchase intention positively and significantly. In addition, customer engagement also mediates the effect of social media marketing on repurchase intention. Therefore, companies should identify the appropriate type of social media according to their products and services to support marketing programs. They should also focus on certain social media to run its marketing program.